Incidence of risk factors in cancer Uruguayan woman’s breast - Perrier Fuentes, José Pedro; Martínez Mrochkovski, Adriana; Más Brochado, Mariana (Cirugía del Uruguay, 1991)
The results of a retrospective study designed to find out the frequency of some of the so-called risk factors for breast cancer in Uruguayan women are presented.